2021
DOI: 10.1038/s41467-020-20491-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging dynamic mTORC1 pathway activity in vivo reveals marked shifts that support time-specific inhibitor therapy in AML

Abstract: Acute myeloid leukemia (AML) is a high remission, high relapse fatal blood cancer. Although mTORC1 is a master regulator of cell proliferation and survival, its inhibitors have not performed well as AML treatments. To uncover the dynamics of mTORC1 activity in vivo, fluorescent probes are developed to track single cell proliferation, apoptosis and mTORC1 activity of AML cells in the bone marrow of live animals and to quantify these activities in the context of microanatomical localization and intra-tumoral het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…Several studies have implicated mTORC1 in apoptosis and cell survival regulation [162][163][164][165]. For example, it has been described that mTOR regulates cell survival after etoposide treatment in acute myeloid leukemia cells (AML) [162].…”
Section: Pi3k-akt-mtor As a Pro-survival/anti-apoptotic Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have implicated mTORC1 in apoptosis and cell survival regulation [162][163][164][165]. For example, it has been described that mTOR regulates cell survival after etoposide treatment in acute myeloid leukemia cells (AML) [162].…”
Section: Pi3k-akt-mtor As a Pro-survival/anti-apoptotic Signalingmentioning
confidence: 99%
“…For example, it has been described that mTOR regulates cell survival after etoposide treatment in acute myeloid leukemia cells (AML) [162]. Furthermore, a recent study showed that inhibition of mTORC1 improved the killing of AML cells by chemotherapy in a time-specific manner [165]. In mouse embryonic fibroblasts (MEFs), mTORC1 can control mitochondrial dynamics and cell survival via MTFP1 [164].…”
Section: Pi3k-akt-mtor As a Pro-survival/anti-apoptotic Signalingmentioning
confidence: 99%
“…Another intriguing therapeutic strategy for targeting metabolic pathways in AML could be through pharmacological modulation of their upstream regulatory signaling pathways, many of which have inhibitors already in clinical use ( 85 ). As one example, the mTOR pathway, which is a long recognized regulator of glucose, lipid and amino acid metabolism, has been recently re-evaluated for AML treatment in combination with standard chemotherapy when given in specific timed manner ( 86 ). Due to the breadth of the field of signaling in metabolic regulation, we refer the readers to other dedicated reviews on the topic ( 85 , 87 , 88 ).…”
Section: Personalized Approaches To Metabolic Targeting Of Amlmentioning
confidence: 99%
“…The mTOR signaling indicator (TOSI) 45 was adapted to build a TOSI-mScarlet-I-NLS (mSc-TOSI) fluorescent reporter targeted to the ATP1A1 locus (Fig. 2a).…”
Section: Atp1a1 As a Selectable Genomic Safe Harbormentioning
confidence: 99%
“…Active mTORC1 signaling results in rapid phosphorylation of the mSc-TOSI phosphodegron by S6K, ubiquitination, and degradation by the proteasome while its inhibition stabilises the reporter (Fig. 2e) 45 . Treatment with rapamycin increased the fluorescence signal confirming the functionality of the reporter construct when expressed from both loci (Fig.…”
Section: Atp1a1 As a Selectable Genomic Safe Harbormentioning
confidence: 99%